Удосконалення системи фінансування дослідницького сектора вищої освіти в Україні як умова розвитку національної економіки - Левченко, О. М.; Жовновач, Р. І.; Хаідура, Ґ. М.; Levchenko, О.; Zhovnovach, R.; Haidura, Hani Mohammad (My University, 2017)
Статтю присвячено висвітленню проблеми інноваційного розвитку дослідницького сектора вищої освіти в Україні та обґрунтуванню новітніх механізмів його фінансування з урахуванням характеру ринкових постіндустріальних трансформацій національної економіки. Розкрито роль освіти та науки в системі формування інноваційної моделі розвитку національної економіки. Проаналізовано основні джерела фінансування науково-дослідницького сектору системи закладів вищої освіти та встановлено їх вплив на ВНЗ в цілому й на науково-дослідницьку діяльність зокрема. Доводиться, що існуюча система фінансування науково-дослідницького сектору системи закладів вищої освіти потребує реформування на основі пошуку та використання альтернативних джерел фінансового забезпечення діяльності. Визначено основні напрями залучення коштів інвесторів недержавного сектору. Обґрунтовано удосконалення системи фінансування науково-дослідницького сектору закладів вищої освіти у рамках їх участі у розвитку глобальних технологічних платформ. The article discloses the issue of innovative development of the research sector of higher education in Ukraine. The newest mechanisms of financing the research sector taking into account the nature of the market post-industrial transformations of the national economy were grounded. The role of education and science in the system of the formation of an innovative model of development of the national economy was disclosed. The main sources of funding of the research sector of the system of higher education institutions have been analyzed. Their influence on higher educational institutions in general and on the research activity in particular was determined. It was proved that the existing system of financing the research sector of the system of higher education institutions needs to be reformed on the basis of the search and application of alternative sources of financial support for the activities. The main directions of attraction of investments of the non-state sector were determined. The improvement of the funding system for the research sector of higher education institutions were grounded.
Іmprovement of financing system of higher education research sector in Ukraine as a condition of the national economy’s development
Keywords: вища освіта; дослідницький сектор; інноваційний розвиток; фінансування; вищі навчальні заклади; higher education; research sector; innovative development; financing; higher educational establishments; higher education institutions